THE DEVELOPMENT OF AN INTERACTIVE WEBSITE ABOUT TAX AND FINANCIAL MANAGEMENT BY APPLYING CONSTRUCTIVISM THEORY FOR STUDENTS OF KING MONGKUT’S UNIVERSITY OF TECHNOLOGY THONBURI - Thanommit, Samonchai (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The development of an Interactive website about tax and financial management by applying constructivism theory for students of King Mongkut’s University of Technology Thonburi. The objectives are 1) to develop a self-learning model through an interaction website to provide knowledge about tax and financial management, by applying constructivism theory 2) to study the quality of an Interactive website 3) to compare academic achievement of students, before and after using an Interactive website, and 4) to study the satisfaction of the sample group of students at King Mongkut’s University of Technology Thonburi after using an Interactive website. The study tools include 1) an interaction website about tax and financial management 2) Website quality assessment form for experts 3) Website satisfaction assessment form 4) Test before and after for students after studying tax and financial management by using an Interactive website. The sample group is bachelor degree of 4th year students of King Mongkut’s University of Technology Thonburi by using a random method, which are 172 people. The creator conducted a study and collected information from experts and used it to develop according to the principles and theories of creating an interactive website for self-learning. Results of the content quality results and technical quality results of the interaction website found to be at a very good level with an average of 4.70 (SD. = 0.33) and 4.53 (SD.1. =0.56) respectively. The satisfaction assessment results from students were at the most satisfactory level, has an average of 4.47 (SD.=0.56) and found that the sample students had an average score of academic achievement after studying through the interactive website, it was significantly higher at the 0.05 level.